2024
DOI: 10.1039/d3dt03261b
|View full text |Cite
|
Sign up to set email alerts
|

Ligand structure and diluent nature in defining improved Am3+ and Cm3+ separation using diglycolamides: a combined solvent extraction and DFT study

A. S. Kanekar,
A. Bhattacharyya,
P. K. Mohapatra

Abstract: Combined effect of marginal Am3+ selectivity of T2EHDGA and Cm3+ selectivity of SO3PhBTP is exploited for the improvement in Am/Cm separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Organic diluents have a significant effect on the extraction behavior of metal ions. , A number of organic diluents of varying polarity were chosen to study the Am 3+ and Cm 3+ separation from a 0.2 M HNO 3 medium containing 1 mM SO 3 PhBTPhen (Figure S1). TODGA and T2EHDGA were chosen as representative DGA derivatives for the diluent variation studies because of their higher solubility in a wide range of organic diluents as compared to other DGA derivatives having shorter alkyl chains. , In our previous report, we observed that among the three aromatic hydrocarbon diluents toluene, t Bu-benzene, and tri iso -propylbenzene, the highest selectivity was observed in the case of toluene, and therefore, in this study, toluene was chosen. Out of the five diluents, namely, n -octanol, iso -decanol, toluene, n -dodecane, and Solvesso-100 (a high solvency C9 aromatic solvent manufactured from petroleum products), the highest extraction efficiency was observed in the case of n -octanol.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Organic diluents have a significant effect on the extraction behavior of metal ions. , A number of organic diluents of varying polarity were chosen to study the Am 3+ and Cm 3+ separation from a 0.2 M HNO 3 medium containing 1 mM SO 3 PhBTPhen (Figure S1). TODGA and T2EHDGA were chosen as representative DGA derivatives for the diluent variation studies because of their higher solubility in a wide range of organic diluents as compared to other DGA derivatives having shorter alkyl chains. , In our previous report, we observed that among the three aromatic hydrocarbon diluents toluene, t Bu-benzene, and tri iso -propylbenzene, the highest selectivity was observed in the case of toluene, and therefore, in this study, toluene was chosen. Out of the five diluents, namely, n -octanol, iso -decanol, toluene, n -dodecane, and Solvesso-100 (a high solvency C9 aromatic solvent manufactured from petroleum products), the highest extraction efficiency was observed in the case of n -octanol.…”
Section: Resultsmentioning
confidence: 99%
“…26 In the case of SO 3 PhBTP, however, the dependence was found to be ∼2 in our previous study. 28 Comparison of Different DGA Derivatives and Aqueous Complexants. The aqueous complexants SO 3 PhBTP, SO 3 PhBTBP, and SO 3 PhBTPhen (Figure 1h,i,j, respectively) were studied for the Am 3+ /Cm 3+ separation along with the seven DGA derivatives as listed in Figure 1; the results are shown in Figures 4 and S3.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
See 3 more Smart Citations